Kinetics and in Vivo Redistribution of 111Indium-Labelled Human Platelets after Intravenous Protamine Sulphate - Heyns, A duP; Lötter, M G; Badenhorst, P N; Kotze, H; Killian, F C; Herbst, C; Reenen, O R van; Minnaar, P C (Thrombosis and Haemostasis, 1980)
The pathogenesis of thrombocytopenia induced by intravenous protamine sulphate was studied in six patients who underwent cardiopulmonary bypass surgery, and in three normal volunteers. Autologous platelets were labelled with 111Indium-oxine. Platelet lifespan was determined. In vivo111In-platelet localization, organ redistribution and sites of destruction were quantitated with a scintillation camera and a computer-assisted imaging system. Protamine induced a transient thrombocytopenia, maximal 5-10 min after injection, and 30-40 min in duration. The thrombocytopenia was accompanied by a transient accumulation of platelets in the liver. The splenic platelet pool remained unaltered and no platelets accumulated in the lungs. Platelet survival, measured in two volunteers, was slightly longer than normal and fitted a linear function best. There was a severe transient neutropenia during the period of thrombocytopenia. We conclude that protamineinduced thrombocytopenia is caused by hepatic accumulation of "activated" platelets or platelet aggregates, the process is reversible, and in the two normal volunteers studied, platelet survival was not affected.
Keywords: Platelet kinetics; 111Indium-oxine labelled human platelets; Protamine sulphate; Thrombocytopenia, protamine induced; Neutropenia, protamine induced